1954
DOI: 10.1079/pns19540011
|View full text |Cite
|
Sign up to set email alerts
|

Economies in Pig and Poultry Feeding

Abstract: access to the open air and received some green food; it would appear that these conditions were necessary, at least in part, to supply factors such as vitamins A and D, riboflavin and vitamin BI2, which are now available as inexpensive dry concentrates. Although American experience with suitably vitaminized soya-maize diets suggests that these are capable of giving good production under intensive conditions, it is questionable whether the supplemented all-vegetable diets at present practicable in the U.K. woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1955
1955
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…'s of the two lots. Finally, Duckworth (1954) tabulated data from some British, Danish and American experiments, found that there was no consistent saving of meal in the groups on the more restricted planes of feeding and concluded that 'restricted feeding of pigs, below the Ministry of Agricultm-e's scale' will save little feed (see Woodman (1952); this scale rises to a maximum of 7 lb. meal/pig/day at 200 lb.…”
Section: A B C a B C A B A S Essexmentioning
confidence: 99%
“…'s of the two lots. Finally, Duckworth (1954) tabulated data from some British, Danish and American experiments, found that there was no consistent saving of meal in the groups on the more restricted planes of feeding and concluded that 'restricted feeding of pigs, below the Ministry of Agricultm-e's scale' will save little feed (see Woodman (1952); this scale rises to a maximum of 7 lb. meal/pig/day at 200 lb.…”
Section: A B C a B C A B A S Essexmentioning
confidence: 99%